Visualisation analysis of project-based learning in mathematics education: a bibliometric study - Wang, Haosheng; Abdul Halim Abdullah,; Wang, Qian (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study aims to conduct a comprehensive bibliometric and visualisation analysis of Project-Based Learning (PjBL) in mathematics education, analysing 242 articles published between 1986 and 2024 from the Web of Science Core Collection and Scopus databases. Utilising CiteSpace software, the study systematically examines research hotspots, themes, and emerging trends through keyword co-occurrence, timeline visualisation, and keyword burst detection. The results indicate a potential increase in annual publications, supported by a statistical curve fitting with an R² value of 0.8405. The United States leads in publication volume, followed by Indonesia and Spain, while China and Australia demonstrate outstanding performance in international collaboration with the highest centrality. The study reveals that although PjBL in mathematics education has attracted considerable research interest, the formation of core author groups remains limited, with only five primary research clusters demonstrating relatively close collaboration. Additionally, ten high-frequency keywords and eleven clusters are identified. Research hotspots in PjBL in mathematics education are categorized into five primary themes: teacher education, interdisciplinary learning, competence development, learning environment, and higher education. The analysis of the temporal and spatial evolution of keywords and burst detection reveals that the top three research frontiers with the highest intensity are statistics education, linear algebra, and mathematical achievement. Furthermore, teacher education, higher education, and technology have emerged as the latest focal points for future research trends.